2009
DOI: 10.1152/japplphysiol.91126.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight effects on T lymphocyte distribution, function and gene expression

Abstract: The immune system is highly sensitive to stressors present during spaceflight. The major emphasis of this study was on the T lymphocytes in C57BL/6NTac mice after return from a 13-day space shuttle mission (STS-118). Spleens and thymuses from flight animals (FLT) and ground controls similarly housed in animal enclosure modules (AEM) were evaluated within 3-6 h after landing. Phytohemagglutinin-induced splenocyte DNA synthesis was significantly reduced in FLT mice when based on both counts per minute and stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
93
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 78 publications
11
93
3
5
Order By: Relevance
“…FLT animals is consistent with previous findings using murine space-flown thymus as well as rat osteoblasts and heart cells [Liu et al, 2000;Kumei et al, 2002;Gridley et al, 2009]. Similar alterations in gene expression were also observed in other stress-related genes involving the GR heterocomplex.…”
Section: Discussionsupporting
confidence: 91%
“…FLT animals is consistent with previous findings using murine space-flown thymus as well as rat osteoblasts and heart cells [Liu et al, 2000;Kumei et al, 2002;Gridley et al, 2009]. Similar alterations in gene expression were also observed in other stress-related genes involving the GR heterocomplex.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, lymphocytes treated with ConA or a combination of ConA and leptin showed no diVerences in the production of IL-2 or the expression of CD25 and CD71. Thus, the data shown in a previous study (Gridley et al 2009) are in agreement with our observations that both cytokine production and expression of activation markers are decreased under microgravity. Additionally, our study reveals that, under microgravity, leptin is not an eVective potentiator of ConA activation and was unable to stimulate cognate lymphocyte responses, inducing IL-2 production and the expression of the activation markers CD25 and CD71.…”
Section: Discussionsupporting
confidence: 93%
“…Spaceflight induces human immune dysfunction accompanied by an accelerated proliferation of pathogenic microbes and may increase the potential risk of infection and malignant transformation in astronauts (Gridley et al, 2009). The effects of spaceflight on the immune system are not caused simply by physical and psychological stress but may also be directly affected by microgravity (Martinelli et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…(2) IFN-c and perforin: IFN-c is a multifunctional cytokine that promotes both adaptive and innate immune responses (Gridley et al, 2009). Studies of flight crews have generally shown that their lymphocytes have diminished IFN-c …”
Section: Discussionmentioning
confidence: 99%